Entangled in the design of a relational materiality: Beyond smart textiles - Bang, Anne Louise; Dumitrescu, Delia; Harsaae, Malene; Ladekarl, Inger Marie; Landin, Hanna; Lewis, Erin; Lastusaari, Mika; Lawrynowicz, Alicja; Miettunen, Kati; Mohan, Mithila; Nyberg, Mikael; Pedersen, Lena; et al. (United Kingdom, 2026)
Nowadays, ethics and care for the environment have shifted paradigms in smart textile design towards responsible energy use and preservation of natural resources. In this research, we aim to relate material science and engineering to textile and interaction design in discovering a vibrant responsive materiality triggered by ultraviolet (UV) energy. The research addresses a bottom-up approach entangling scientific development in material science, textile craftsmanship, and design to the understanding of human use and the capacities for change of this natural phenomena. Compared to a conventional textile design process where material and form composition connect in a final expression, this research positions designers and scientists as enablers of material relations. The artefacts, therefore, exhibit multiple states and forms, transforming dynamically through use and sensitivity to natural phenomena. The selected textile artefacts are seen as relational; they open for different conversations and materialize entanglements of materials, techniques, methods, and research methodologies that relate experimental research to human-centered and more-than-human approaches.
Proceedings of Nordes 2025: Relational Design